The Strength of Authenticity in Developing Rural Tourism (A Case Study of Tri Eka Buana Village) - I Gusti Agung Putu Sri Mahadewi; I Nyoman Suamir; Nyoman Mastiani Nadra; I Ketut Suarta; Ida Ayu Elistyawati (International Journal of Glocal Tourism, 2022)
Purpose: This study aims to determine the strategies used in the authenticity of Tri Eka Buana Village, Bali, Indonesia, as a tourist attraction. Research methods: This research is a research mixed method with analytical techniques using the Internal Factor Analysis (IFAS), External Factor Analysis (EFAS), Internal-External Matrix (IE), SWOT, and Quantitative Strategic Planning Matrix (QSPM) Analysis. Findings: Based on the results of the IFAS matrix analysis, the main strength is that it has beautiful natural and artificial potential such as Bukit Abah, Danu Seliwah Temple, Dukuh Sakti Waterfall, Umananing Malini dance and Balinese Arak that can attract tourists, while the main weakness is that access to tourist objects is inadequate, such as a narrow and irregular parking area. Based on the results of the EFAS matrix analysis, it is known that the main opportunity is the development of Tri Eka Buana Village by involving local communities so as to minimize unemployment, preserve cultural and natural traditions while the main threat faced is competition between other tourism objects that have developed. The results of the IE Matrix research place the village in theposition Growth (Cell I). Implication: SWOT analysis resulted in 8 alternative strategies of authenticity from the 8 strategies, 3 priority strategies were obtained and have been calculated through the QSPM Matrix with a total TAS of 194.13, 193.57, and 186.46, namely optimizing the potential promotion of Tri Eka Buana Village Karangasem Bali through the media. social media such as Instagram, Facebook, and websites.